Analysis of plumage, morphology, and voice reveals species-level differences between two subspecies of Prevost’s Ground-sparrow Melozone biarcuata (Prévost and Des Murs) (Aves: Emberizidae) - Sandoval, Luis; Bitton, Pierre-Paul; Doucet, Stéphanie M.; Mennill, Daniel J. (Zootaxa, 2014)
Melozone biarcuata (Prevost’s Ground-sparrow) has traditionally been divided into two allopatric groups based on differences in vocalizations and plumage characteristics: M. b. cabanisi in Costa Rica and M. b. biarcuata/M. b. hartwegi in northern Central America. However, the relationship between these subspecies has not been studied using a modern taxonomic approach. In this study, our objective was to provide the first detailed taxonomic comparison between these three subspecies using an integrative multi-trait analysis. We analyzed morphometric features, qualitative plumage patterns, and quantitative plumage measurements using spectral reflectance from all three subspecies, and we analyzed vocalizations for subspecies M. b. biarcuata and M. b. cabanisi. Our results show that M. b. cabanisi can be readily distinguished from the two other subspecies on the basis of morphometrics (M. b. cabanisi are smaller), plumage patterns (M. b. cabanisi have different facial markings and plumage patches), color differences (M. b. cabanisi have plumage patches that differ in color and brightness), and vocalizations (M. b. cabanisi have songs and calls that are acoustically distinct from those of M. b. biarcuata). By contrast, the two northern subspecies M. b. biarcuata and M. b. hartwegi were very similar for most traits, supporting previous suggestions that the two northern subspecies should be considered a single subspecies. Our data reveal that the differentiation in phenotypic characteristics between M. b. cabanisi versus M. b. biarcuata and M. b. hartwegi is similar to that reported for other complexes of subspecies where species status has been recognized. We argue that M. b. cabanisi should be treated as a species separate from M. biarcuata and propose that it be called Melozone cabanisi, White-faced Ground-sparrow. Our findings will contribute to the conservation efforts of the White-faced Ground-sparrow, which is endemic to Costa Rica’s Central Valley and Turrialba Valley, by bringing focus to conservation policies that preserve ground-sparrow habitat (thickets, shade coffee plantations, and young secondary forest).